Analysis of age discrimination in the rental housing market in Japan: An approach using a fair housing audit - Masayuki Nakagawa (Osaka University, Institute of Social and Economic Research (ISER), 2003)
A fair housing audit is an important tool for measuring racial and ethnic discrimination in housing market, so they are widely used for policy purposes in the U.S. Each audit consists of a visit to a real estate agent by a minority individual and a majority individual with equal qualification. This paper applies this survey technique to age discrimination in Japanese rental housing market. Using data from the 2001 Osaka Audits, this paper analyzes the level and causes of the discrimination encountered by elderly home-seekers, and argues the relation between age discrimination and residential segregation of elderly. The estimated level of discrimination is high: The number of available housing units about which elderly home-seekers are told is 30 percent fewer than the number of available housing units about which young home-seekers are told. Econometric tests suggest that stereotyping about elderly renters' ability to pay and rental terms, and young people's preference for a neighborhood of young inhabitants influences agent behavior. And age discrimination and inflexibility in the housing market for the elderly are probable reason for residential segregation of elderly.
Keywords: 330; Vermietung von Immobilien; Diskriminierung; Altersgruppe; Alte Menschen; Japan